Availability management of hotel rooms under cooperation with online travel agencies. (September 2015) - Ling, Liuyi; Dong, Yufeng; Guo, Xiaolong; Liang, Liang
Highlights: Proposes an availability management method for hotels when cooperating with OTAs. Allows hotels to decide when to send unavailable signal to their cooperative OTAs. Suggests customers to check hotel's host website if hotel rooms are unavailable at OTAs. Abstract: Hotels are required to pay high commission fees when cooperating with online travel agencies (OTAs) to manage online marketing channels. Thus, to maximize their revenues, hotels protect their income through their own (traditional) marketing channels and save on considerable commissions by optimizing room availability for their cooperative OTAs. The present paper proposes a method to manage such availability in the context of a hotel cooperating with an OTA on room booking service. Customers can make reservations directly through the distribution channel of the hotel or indirectly through the OTA, if applicable, during the selling period. The hotel then forecasts room demand base on distribution information after receiving enough room bookings and optimizes room availability with respect to its maximum revenue by determining whether on-hand rooms are available for the OTA. Results indicate when hotel rooms become unavailable for the cooperative OTA. Numerical studies reveal that this method is conducive to the improvement of hotel revenue.